Phase behavior-microstructure-crystallization kinetics correlations in semi-crystalline/amorphous PCL/SAN mixtures filled with nanosilica - Salkhi Khasraghi, Samaneh; Khonakdar, Hanieh; Hemmati, Farkhondeh; Zarei, Sara; Miri, Fatemeh Sadat; Nobre, Marcos A.L. [UNESP]; Khonakdar, Hossein Ali (Scientific Scholar, 2024)
In this study, the effects of poly(ε-caprolactone) (PCL) molecular weight and the type and presence of nanosilica on the non-isothermal crystallization behavior of PCL in the PCL/poly(styrene-co-acrylonitrile) (SAN)/nanosilica systems have been quantitatively investigated. The PCL/SAN system have been chosen as an ideal model system because of the special phase behavior of the blends, which include a lower-critical solution temperature (LCST) phase diagram over a virtual upper-critical solution temperature. By this choose, the great importance of phase separation, mutual phase dissolution and preferential nanoparticle migration to one of the polymeric phases on the crystallization behavior during a commercial production process has been highlighted. The addition of both hydrophilic (Si) and hydrophobic (SiR) silica nanoparticles to virgin PCLs with different molecular weights retards the crystallization process. However, the presence of these nanoparticles in PCL/SAN blends impacts the PCL crystallization kinetics in opposite ways, depending on the nanosilica type, PCL molecular weight and melt cooling rate. The reasons for the observed opposite trends are the changes in the LCST-type phase diagram position by altering the PCL molecular weight and nanosilica type, the selective migration of nanoparticles as well as the dispersion state of nanofillers. The presence of both Si and SiR nanosilicas increases the crystallization activation energy, respectively, by 4.2% and 2.4% for the PCL/SAN blend conatining the PCL with lower molecular weight. While the addition of both Si (11%) and SiR (6.7%) reduces this energy for the blend conatining the PCL with higher molecular weight.
Keywords: Blends; Crystallization; Nanocomposite; Phase behavior; Poly(ε-caprolactone)